Analytical and finite element modelling of hydraulic bulge test on extra deep drawing steel with fractography study. Issue 4 (2nd October 2021) - Sannidhi, Anvesh Krishna; Gupta, Amit Kumar; Varghese, George; Toshniwal, Krishna; Sharma, Vaibhav
ABSTRACT: In this paper, analytical, finite element modelling (FEM) and experimental studies are conducted on the biaxial stretching of extra deep drawing steel sheet using hydraulic bulge test, where the true plastic strain exceeds 70%, in contrast to the 20–30% strain achieved in the conventional uniaxial tensile test. The analytical modelling includes four different approaches, namely, Hill, Panknin, Chakrabarty and Kruglov. FEM is done using three yield criteria, Hill-48, Barlat-89 and Barlat-2000. Experimental results show that the stress-strain relationship using bulge radius based on Panknin approach and thickness based on Kruglov approach in the analytical study and using Barlat-2000 yield model in FEM study are in close agreement with the experimental curve. Fractography study, conducted on specimens from tensile and bulge test, reveals/confirms the presence of more deep elongated shear dimples in bulge test compared to equiaxed dimples in the tensile test. This corroborates with the experimental results of achieving the high level of plastic deformation till fracture in the hydraulic bulge test.